RT-PCR and Dot Blot hybridization methods for a universal detection of tospoviruses - EIRAS, MARCELO (2001)
Transcriptase reverse - polymerase chain reaction (RT-PCR) and dot blot hybridization with digoxigenin-labeled probes were applied for the universal detection of Tospovirus species. The virus species tested were Tomato spotted wilt virus, Tomato chlorotic spot virus, Groundnut ringspot virus, Chrysanthemum stem necrosis virus, Impatiens necrotic spot virus, Zucchini lethal chlorosis virus, Iris yellow spot virus. Primers for PCR amplification were designed to match conserved regions of the tospovirus genome. RT-PCR using distinct primer combinations was unable to simultaneously amplify all tospovirus species and consistently failed to detect ZLCV and IYSV in total RNA extracts. However, all tospovirus species were detected by RT-PCR when viral RNA was used as template. RNA-specific PCR products were used as probes for dot hybridization. This assay with a M probe (directed to the G1/G2 gene) detected at low stringency conditions all Tospovirus species, except IYSV. At low stringency conditions, the L non-radioactive probe detected the seven Tospovirus species in a single assay. This method for broad spectrum detection can be potentially employed in quarantine services for indexing in vitro germplasm.